(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article will talk about the views of the Turkic Ulus and Turkic peoples, as well as his practical work on this issue. In addition, the article also reflects on the history and ethnic similarities of the shalling of the Uzbek people.